Data on the construction of a recombinant HEK293 cell line overexpressing hERG potassium channel and examining the presence of hERG mRNA and protein expression - Yi, Fan Teah; Abduraman, Muhammad Asyraf; Amanah, Azimah; Adenan, Mohd Ilham; Sulaiman, Shaida Fariza; Mei, Lan Tan (Elsevier, 2017)
The data presented in this article are related to the research article entitled “The effects of deoxyelephantopin on the cardiac delayed rectifier potassium channel current (IKr) and human ether-a-go-go-related gene (hERG) expression” (Y.F. Teah, M.A. Abduraman, A. Amanah, M.I. Adenan, S.F. Sulaiman, M.L. Tan) [1], which the possible hERG blocking properties of deoxyelephantopin were investigated. This article describes the construction of human embryonic kidney 293 (HEK293) cells overexpressing HERG potassium channel and verification of the presence of hERG mRNA and protein expression in this recombinant cell line.